Strategy to Increase the Effectiveness of Investigating Corruption Crimes by Law Enforcement Officials in Indonesia - Simbolon, Dian Lorenjaya; Debora, Debora (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
In Indonesia, corruption has gotten to be a genuine issue that should be tended to in arrange to preserve the judgment of the legitimate framework and the functioning of the government. The reason of this study is to assess strategies that will be utilized to extend the capacity of the lawful framework to combat corruption in Indonesia. This study indicates that some of the main issues in preventing corruption include poor coordination among law enforcement agencies, brittle bodies, and political interventions that undermine the autonomy of law enforcement agencies. By implementing comprehensive and progressive strategies, anti-corruption measures can be strengthened, corruption offenders can be prosecuted, and the Indoneian legal system can be strengthened.